Some Generalized Inequalities Involving Local Fractional Integrals and their Applications for Random Variables and Numerical Integration - Erden, Samet; Sarikaya, M. Z.; Celik, N.; Erden, Samet (Sciendo, 2016)
We establish generalized pre-Gruss inequality for local fractional integrals. Then, we obtain some inequalities involving generalized expectation, p-moment, variance and cumulative distribution function of random variable whose probability density function is bounded. Finally, some applications for generalized Ostrowski-Gruss inequality in numerical integration are given.
Keywords: Gruss Inequality; Ostrovski Inequality; Local Fractional Integrals; Random Variables